IDNLearn.com: Where your questions are met with thoughtful and precise answers. Get prompt and accurate answers to your questions from our community of knowledgeable experts.
Sagot :
To identify the 42nd term of an arithmetic sequence, given that the first term [tex]\(a_1 = -12\)[/tex] and the 27th term [tex]\(a_{27} = 66\)[/tex], follow these steps:
1. Identify the formula for the nth term of an arithmetic sequence:
[tex]\[ a_n = a_1 + (n-1) \cdot d \][/tex]
2. Use the information for the 27th term to determine the common difference [tex]\(d\)[/tex]:
- Given [tex]\(a_{27} = 66\)[/tex],
- Substitute into the formula: [tex]\( 66 = -12 + (27-1) \cdot d \)[/tex],
- Simplify the equation: [tex]\( 66 = -12 + 26 \cdot d \)[/tex],
- Solve for [tex]\(d\)[/tex]:
[tex]\[ 66 + 12 = 26 \cdot d \implies 78 = 26 \cdot d \implies d = \frac{78}{26} = 3. \][/tex]
3. Calculate the 42nd term using the found value of the common difference:
- We need to find [tex]\(a_{42}\)[/tex],
- Use the nth term formula: [tex]\( a_{42} = a_1 + (42-1) \cdot d \)[/tex],
- Substitute the known values:
[tex]\[ a_{42} = -12 + (42-1) \cdot 3, \][/tex]
- Simplify the equation:
[tex]\[ a_{42} = -12 + 41 \cdot 3 , \][/tex]
- Calculate the value:
[tex]\[ a_{42} = -12 + 123 = 111. \][/tex]
So, the 42nd term of the arithmetic sequence is 111. Therefore, the correct answer is:
111
1. Identify the formula for the nth term of an arithmetic sequence:
[tex]\[ a_n = a_1 + (n-1) \cdot d \][/tex]
2. Use the information for the 27th term to determine the common difference [tex]\(d\)[/tex]:
- Given [tex]\(a_{27} = 66\)[/tex],
- Substitute into the formula: [tex]\( 66 = -12 + (27-1) \cdot d \)[/tex],
- Simplify the equation: [tex]\( 66 = -12 + 26 \cdot d \)[/tex],
- Solve for [tex]\(d\)[/tex]:
[tex]\[ 66 + 12 = 26 \cdot d \implies 78 = 26 \cdot d \implies d = \frac{78}{26} = 3. \][/tex]
3. Calculate the 42nd term using the found value of the common difference:
- We need to find [tex]\(a_{42}\)[/tex],
- Use the nth term formula: [tex]\( a_{42} = a_1 + (42-1) \cdot d \)[/tex],
- Substitute the known values:
[tex]\[ a_{42} = -12 + (42-1) \cdot 3, \][/tex]
- Simplify the equation:
[tex]\[ a_{42} = -12 + 41 \cdot 3 , \][/tex]
- Calculate the value:
[tex]\[ a_{42} = -12 + 123 = 111. \][/tex]
So, the 42nd term of the arithmetic sequence is 111. Therefore, the correct answer is:
111
Your participation means a lot to us. Keep sharing information and solutions. This community grows thanks to the amazing contributions from members like you. Thank you for trusting IDNLearn.com with your questions. Visit us again for clear, concise, and accurate answers.